KONTRIBUSI INTELLECTUAL CAPITAL DAN TAX AGGRESSIVENESS TERHADAP NILAI PERUSAHAAN JASA KEUANGAN DI INDONESIA - Muhammad Yusuf (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
This research is aimed to analyze the effect of intellectual capital and tax planning on firm value. The study examined the relationship of intellectual capital variables is Value Added Capital Employed (VACE), Value Added Human Capital (VAHC), Value Added Structural Capital (VASC). Variable tax aggressiveness measured by using tax rate 25% at less Effective Tax Rate (ETR) in multiply Pre Tax Book Income. And variable values firm measured by Price Book Value (PBV). This research use secondary data analysis of financial statement or annual report of firms in Indonesia Stock Exchange. Population in this research was financial sector companies that listed in Indonesia Stock Exchange in 2013-2016. Using the method purposive sampling, sample collected in this research was sample as many as 52 the annual financial report. The methodology used in this research was the simple linier regression by using SPSS 22. This research result indicates that the intellectual capital has significant influence on firm value. tax aggressiveness has negative significant influence on firm value. And simultaneously intellectual capital and tax planning has significant influence on firm value.